La aspiración de origen nasal en la evolución fonológica del euskera: un caso de 'rhinoglottophilia' - Igartua, Iván (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2008)
From a typological perspective, the diachronic correspondence -n- > -h- is perhaps the most marked development in the phonological history of the Basque language. The examples of such a process of sound change are extremely scarce around the world and have not been widely known until recent times. This is surely the reason why some scholars have tended to explain the historical replacement of -n- by -h- at the onset of the second syllable as a result of two different and completely unrelated processes of loss (of the nasal resonant) and insertion of an aspiration (with an allegedly antihiatic function). But since J. Matisoff's (1975) pioneering work on rhinoglottophilia, the mysterious connection between glotality and nasality, a new perspective has opened up for the typological assessment of that class of sound change processes to which the Basque diachronic correspondence clearly belongs. The present article constitutes an attempt to dissipate every remaining and possible doubt concerning the typological verisimilitude of this Basque development, which is itself probably the best instance we have of the reanalysis of nasalization as aspiration, one of the two main processes of change that can be triggered by rhinoglottophilia (the oher one, the reanalysis of aspiration as nasalization, is better attested cross-linguistically). Among the concluding remarks of the study, a detailed diachronic explanation of the phonetic as well as phonological sides of the sound change in question is also offered.